1995
DOI: 10.1042/bj3110905
|View full text |Cite
|
Sign up to set email alerts
|

Urea-induced inactivation and denaturation of clostridial glutamate dehydrogenase: the absence of stable dimeric or trimeric intermediates

Abstract: Urea-induced effects in clostridial glutamate dehydrogenase (GDH, EC 1.4.1.2) were studied by spectrophotometry, circular dichroism, FPLC, affinity chromatography and PAGE. Denaturation of enzyme occurred over a narrow range of urea concentrations (2.5-3.5 M), accompanied by inactivation of enzyme with a similar rate constant. The contribution of instantaneous inhibition by urea was also ascertained. FPLC studies of urea-treated GDH gave no evidence for dissociated oligomeric fragments of the hexamer in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…Most GDHs are hexamers composed of identical subunits arranged as a dimer of trimers [1][2][3][4][5][6][7][8][9][10][11][12]. A number of studies of the unfolding of both soluble and immobilized GDHs in the presence of denaturing agents such as guanidinium chloride (GdmCl) and urea have been made [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. For the clostridial enzyme, for which a high-resolution structure is available [10], it was concluded that, at concentrations of GdmHCl insufficient to cause denaturation, the hexamer dissociates into inactive trimers without any gross structural changes that could be detected by fluorescence or CD [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most GDHs are hexamers composed of identical subunits arranged as a dimer of trimers [1][2][3][4][5][6][7][8][9][10][11][12]. A number of studies of the unfolding of both soluble and immobilized GDHs in the presence of denaturing agents such as guanidinium chloride (GdmCl) and urea have been made [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. For the clostridial enzyme, for which a high-resolution structure is available [10], it was concluded that, at concentrations of GdmHCl insufficient to cause denaturation, the hexamer dissociates into inactive trimers without any gross structural changes that could be detected by fluorescence or CD [20].…”
Section: Introductionmentioning
confidence: 99%
“…NAD + alone was also effective but 2-oxoglutarate was not, in striking contrast with the opposite pattern for protection of this enzyme against unfolding in urea [Aghajanian, Martin and Engel (1995) Biochem. J.…”
mentioning
confidence: 99%
“…To unfold and separate the subunits [28], the two proteins, each at 1.5 mg\ ml protein concentration in 0.1 M potassium phosphate buffer (pH 7.0), were incubated separately at 25 mC in 4.5 M urea for 60 min (triple mutant) or 4 M urea for 30 min (C320S). The two denatured enzymes (residual activities 1 %) were mixed at a 1 : 5 (triple mutant :C320S) volume ratio, diluted 25-fold into 0.1 M potassium phosphate buffer (pH 7.0) containing 2 mM NAD + , and incubated at 25 mC for 36 h for refolding and reactivation as described previously [16].…”
Section: Construction Of Inter-subunit Hybridsmentioning
confidence: 99%
“…In other words, as viewed from the energy landscape theory or the folding funnel concept [3 -7], the native state of a protein is that minimally frustrated heteropolymer with a rugged funnel-like landscape biased towards the native structure [8,9]. The particular conformation taken by the protein influences its biological activity [10,11] and this has influenced the comparison though by limited authors, of the conformation and activity changes during the course of enzyme denaturation [12].…”
Section: Introductionmentioning
confidence: 99%